Effect of Welding Orientation in Angular Distortion in Multipass GMAW - Lucas Martins Garcia; Verônica Teixeira Noronha; João Ribeiro (Journal of Manufacturing and Materials Processing, 2021)
The use of the welding process on an industrial scale has become significant over the years and is currently among the main processes for joining metallic materials. Along the weld, structural changes occur in the vicinity of the joint. These thermal stresses and geometric distortions are mostly undesirable and are complex to predict with precision. Using S235JR steel as the base material, laboratory experiments were carried out using the multipass GMAW process, with the aim of investigating the influence of the welding direction on angular distortion. To measure the distortions, a methodology was applied using equipment to identify the coordinates in the operational space with metrological precision. Through metrological and statistical analyses, we found that the orientation factor significantly influenced the final distortions and that the alternated orientation sequence resulted in less distortions.